Peningkatan Kemampuan Guru dalam Menyusun RPP Berbasis Karakter melalui Pendekatan Supervisi Kalaboratif Di SDN 07 Situjuah Gadang Kecamatan Situjuah Limo Nagari - Ridwan Ridwan (JPGI (Jurnal Penelitian Guru Indonesia), 2020)
The success of teaching and learning activities can be known from the results of teacher performance in preparing character-based lesson plans and implementing them in the teaching and learning process in class. This school action research aims to see whether there is an increase in the ability of teachers in developing character-based lesson plans and their implementation in teaching and learning process. This research uses 2 cycles. The research procedure has four stages of activities are, planning, action, observation and evaluation, and reflecting. The study was conducted at SDN 07 Situjuah Gadang. The subject of the research is the class teacher and subject teacher, which totals 7 teachers. Data processing using qualitative descriptive analysis techniques.Based on the results of data analysis that has been stated, that the data obtained from observing the ability of teachers to prepare character-based lesson plans in cycle I and cycle II there is an increase in the ability of teachers in preparing character-based lesson plans.